The Impact of Spinopelvic Mobility on Arthroplasty: Implications for Hip and Spine Surgeons - Haffer, Henryk (J Clin Med, 2020)
Spinopelvic mobility represents the complex interaction of hip, pelvis, and spine. Understanding this interaction is relevant for both arthroplasty and spine surgeons, as a predicted increasing number of patients will suffer from hip and spinal pathologies simultaneously. We conducted a comprehensive literature review, defined the nomenclature, summarized the various classifications of spinopelvic mobility, and outlined the corresponding treatment algorithms. In addition, we developed a step-by-step workup for spinopelvic mobility and total hip arthroplasty (THA). Normal spinopelvic mobility changes from standing to sitting; the hip flexes, and the posterior pelvic tilt increases with a concomitant increase in acetabular anteversion and decreasing lumbar lordosis. Most classifications are based on a division of spinopelvic mobility based on ΔSS (sacral slope) into stiff, normal, and hypermobile, and a categorization of the sagittal spinal balance regarding pelvic incidence (PI) and lumbar lordosis (LL) mismatch (PI–LL = ± 10° balanced versus PI–LL > 10° unbalanced) and corresponding adjustment of the acetabular component implantation. When performing THA, patients with suspected pathologic spinopelvic mobility should be identified by medical history and examination, and a radiological evaluation (a.p. pelvis standing and lateral femur to L1 or C7 (if EOS (EOS imaging, Paris, France) is available), respectively, for standing and sitting radiographs) of spinopelvic parameters should be conducted in order to classify the patient and determine the appropriate treatment strategy. Spine surgeons, before planned spinal fusion in the presence of osteoarthritis of the hip, should consider a hip flexion contracture and inform the patient of an increased risk of complications with existing or planned THA.